Communication Strategi of Field Agricultural Extension in Postharvest Technology Development for Corn in the Mulia Bakti Farmers Group, Sumuran Village, Batangtoru Subdistrict, South Tapanuli Regency, North Sumatera - Pasaribu, Ali Imam Arrasyid (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to analyze the communication strategy of extension workers field agriculture in the development of corn postharvest technology in mulia bakti farmer group, sumuran village, batangtoru district, district south tapanuli, north sumatra province, as well as analyzing the barriers and the efforts made by field agricultural instructors in delivering post-harvest messages or information to the mulia bakti farmer group. Paradigm method used is the constructivism paradigm with qualitative and qualitative methods data collection techniques through in-depth interviews and observation. Subject the research is the field agricultural extension officer in sumuran village and members of the mulia bakti farmer group in sumuran village. The results show the strategy communication carried out by ppl, namely (1) Ppl as a communicator for increasing the confidence of farmers must increase knowledge and have the ability in agriculture by participating in training. (2) Identifying audiences by education level and age. (3) Convey messages and information in a persuasive, gentle, and repetitive manner. (4) The communication channel chosen is direct visits to the land as well as to the farmer's house and if there is something important the farmer can contact ppl by cell phone. Barriers experienced by ppl exist two, namely technical and ecological barriers. The technical barrier is the level of low understanding of the material by farmers. Steps were taken by ppl to pay special attention and provide repeated counseling until they understand and activate the group's function, namely as a forum for exchanging ideas.